Quantitative Assessment of Psychological Stress Changes Before and After Ureteral Stent Placement: A Prospective Observational Study - Fu Y; Liang P; Gao X; Mo Z; Ruan Y; Pan J (Patient Preference and Adherence)
Yijun Fu,1,* Puzhao Liang,2,* Xin Gao,1,* Zimei Mo,1 Yongtong Ruan,2 Jie Pan2 1Department of Urology, Yangjiang Hospital of Traditional Chinese Medicine, Affiliated to Guangzhou University of Chinese Medicine, Yangjiang, Guangdong, People’s Republic of China; 2Department of Urology, Yangjiang Hospital of Traditional Chinese Medicine, Yangjiang, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongtong Ruan, Department of Urology, Yangjiang Hospital of Traditional Chinese Medicine, Shiwan North Road, Jiangcheng District, Yangjiang, 529500, People’s Republic of China, Tel +86-13432578081, Email ruanyongtong@qq.comBackground: Ureteral stents are commonly used in urological procedures, with approximately 2 million placements annually worldwide. While physical complications are well-documented, psychological impacts remain understudied. This study aimed to quantitatively evaluate psychological stress changes before and after ureteral stent placement in order to better understand patients’ psychological needs during this common urological procedure.Methods: This prospective observational study with paired before-after measurements was conducted at Yangjiang Hospital of Traditional Chinese Medicine between November 2024 and March 2025. We enrolled 82 patients who underwent ureteral stent placement following ureteroscopic lithotripsy. Psychological assessments using the Chinese version of the Perceived Stress Scale and Emotional Distress Inventory were performed at two time points: immediately before stent insertion and during the stent indwelling period. Data were analyzed using paired t-tests, ANOVA, and multiple linear regression.Results: Total perceived stress scores increased significantly from baseline to stent indwelling period (14.40± 9.85 vs 23.90± 10.06, p< 0.001), representing a 66.0% increase. The tension dimension demonstrated the most pronounced change (77.8% increase: from 6.40± 3.32 to 11.38± 5.12, p< 0.001), while helplessness increased by 56.5% (from 8.00± 7.09 to 12.52± 6.62, p< 0.001). Secondary analyses showed significant gender differences, with females reporting higher helplessness scores than males (12.32± 8.00 vs 4.44± 3.37, p< 0.001). Stent duration ≥ 1 month was associated with greater helplessness compared to < 1 month (12.97± 6.95 vs 9.64± 2.66, p=0.006). Emotional distress analysis revealed anhedonia in 75.6– 79.3% of patients, while emotional fluctuations were less common (14.6– 45.1%). Multiple regression confirmed gender as an independent predictor of helplessness (β=− 0.371, p=0.001).Conclusion: Ureteral stent placement significantly increases psychological stress, particularly tension and helplessness dimensions. Female patients and those with prolonged stent duration are at higher risk for psychological distress. Clinicians should proactively address patients’ psychological needs through targeted patient education, especially for high-risk populations, to improve patient experience during the stent indwelling period.Keywords: ureteral stent, psychological stress, gender differences, patient education